Measuring Robustness of the Postural Control System to a Mild Impulsive Perturbation - Hur, Pilwon; Duiser, Brett A.; Salapaka, Srinivasa M.; Hsiao-Wecksler, Elizabeth T. (IEEE transactions on neural systems and rehabilitation engineering, 2010)
We propose a new metric to assess robustness of the human postural control system to an impulsive perturbation (in this case, a mild backward impulse force at the pelvis). By applying concepts from robust control theory, we use the inverse of the maximum value of the system's sensitivity function ( 1/MaxSens ) as a measure for robustness of the human postural control system, e.g., a highly sensitive system has low robustness to perturbation. The sensitivity function, which in this case is the frequency response function, is obtained directly using spectral analysis of experimental measurements, without need to develop a model of the postural control system. Common measures of robustness, gain and phase margins, however require a model to assess system robustness. To examine the efficacy of this approach, we tested thirty healthy subjects across three age groups: young (YA: 20-30 years), middle-aged (MA: 42-53 years), and older adults (OA: 71-79 years). The OA group was found to have reduced postural stability during quiet stance as detected by center of pressure measures of postural sway. The proposed robustness measure of 1/MaxSens was also found to be significantly smaller for OA than YA or MA ( p =0.001), implying reduced robustness among the older subjects in response to the perturbation. Gain and phase margins failed to detect any age-related differences. In summary, the proposed robustness characterization method is easy to implement, does not require a model for the postural control system, and was better able to detect differences in system robustness than model-based robustness metrics.